Noninvasive Assessment of Nonalcoholic Fatty Liver Disease in Children with Overweight and Obesity by Transient Elastography - Mohamed Fajrudheen; Samarendra Mahapatro; Manas K. Panigrahi; Suprava Naik; Amit K. Satapathy (Indian Journal of Endocrinology and Metabolism)
Introduction: Childhood obesity and nonalcoholic fatty liver disease (NAFLD) are emerging as significant health concerns. While liver biopsy remains the gold standard for diagnosis, there is a pressing need for a noninvasive alternative to identify early fibrosis. Methods: A cross-sectional investigation was carried out from January 2020 to December 2021 involving overweight and obese children attending the pediatric outpatient department (OPD). The aim is to determine the occurrence of fibrotic and steatotic changes in the liver of overweight and obese children using transient elastography (TE) and to establish correlations between TE results, Pediatric NAFLD Fibrosis Index (PNFI), and other biochemical parameters. TE was utilized to assess both fibrotic and steatosis changes, while ultrasound (USG) was employed to detect steatosis in the liver. Results: Two hundred and fifty-nine eligible children participated in the study. Mean age of the study cohort was 10.8 years, with males constituting 63%. Mean Z score for BMI was 1.71 ± 0.57. Fibrosis was detected in 29.3% of children by TE, while steatosis was observed in 27.7% of children. Steatosis was identified in 23.8% of cases through USG. BMI Z score, ALT (Alanine aminotransferase), AST and PNFI score exhibited significant associations with grades of liver fibrosis and steatosis as determined by TE, as well as with grades of steatosis according to USG findings. Conclusion: A notable prevalence of increased liver stiffness was observed in overweight and obese children. TE proves to be a valuable tool in identifying fibrotic and steatotic changes in these children, complementing existing noninvasive modalities.